EKSTENSI DAN INVASI INTRAKRANIAL TUMOR KULIT KEPALA: TANTANGAN DIAGNOSIS DAN TATALAKSANA - Sophie Yolanda; Tiara Aninditha; Henry Riyanto Sofyan; Rahmad Mulyadi (NEURONA, 2022)
Scalp tumors are quite rare, only 1-2% are malignant and have a tendency for intracranial extension and invasion. This extension can lead to various neurological complications, such as cancer pain, increased intracranial pressure (ICP), and other neurological deficits. A 37-year-old woman presented with decreased consciousness since 2 days earlier. The patient had a history of lump on the top of her head since 4 years, repeated 3 times after resection without previous treatment. On the third recurrence, the tumor was enlarged until it some part of the tumor can be seen depressed against the skull and this part was painful. The pain worsened throughout the entire head accompanied by visual field disturbance of right inferior homonymous quadranopia, right central facial nerve paresis, and right hemiparesis. Contrast head CT scan revealed lobulated heterogeneous lesion in the parietooccipital region, extending to the extraaxial and intracerebral, accompanied by vasogenic edema with destruction of the parietal and occipital bones. The result of histopathology is trichilemmal carcinoma. The patient received morphine drip therapy 10mg/24 hours for the cancer pain, which was then replaced with its patch equivalent dose, dexamethasone 2x10mg IV tapering off gradually according to the clinical condition, gabapentin 2x300mg, and wholebrain radiotherapy (WBRT) 30 Gy in 10 sessions. The patient was discharged in conscious condition and her pain resolved to mild pain. Keywords: cancer pain, increased intracranial pressure, intracranial invasion, scalp tumor